Hubungan Tingkat Kecemasan dengan Tingkat Nyeri pada Pasien Post Operasi Kanker Payudara di Bangsal Bedah RSUP dr. M. Djamil Padang 2024 - Firda Damba Wahyuni; Ira Sri Budiarti (Sekolah Tinggi Ilmu Kesehatan YPAK Padang, 2024)
The incidence of breast cancer in the world is very high, reported that the incidence of breast cancer is 20% of all malignancies. This research used descriptive correlation by designed cross sectional study that was conducted in RSUP dr. M Djamil Padang from January-february 2024. The samples of this research were 44 peoples that consisted by postoperative lumbektomi and mastektomi 1-3 days. Techniques of data collection were Primer data that gotten from Questioner research by respondent and secondary data were obtained from health workers. The data processed by computerized and the data analyzed by univariate analysis with frequency distribution and bivariate analysis of data with statistical test Chi-Square . The result of the study by 44 respondents who experienced pain level was as much as 19 peoples (43,2 %), and respondents who experienced anxiety level was as much as 32 peoples (72,7%). Bivariate analysis, obtained the result p > 0,05 it’s mean that there is no relationship anxiety level with the level of pain (p=0,118) in the RSUP dr. M. Djamil Padang 2024. Based on the result of the study are expected to the health workers to always giving motivation to each patients postoperative of breast cancer that they can they can through a sense of anxiety and pain they felt after the holding of the operation. Key word: Anxiety level; painful level;